Pengaruh Profitabilitas Dan Leverage Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Intervening dimasa Pandemi - Afira, Nurul; Wijaya, Anggi Hadi; Fitri, Wahyu (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
The purpose of this study was to determine how big the influence of profitability and leverage on firm value with financial performance as an intervening variable during the pandemic in the Property & Real Estate Industry Sector Period (2016-2020). in property & real estate companies listed on the Indonesian stock exchange in 2016-2020 a total of 65 companies. While the sample of this study consisted of 38 companies included in property & real estate companies and were selected by purposive sampling. The analytical method used is multiple linear regression data analysis, using computer assistance with SPSS 21 software program. There is no significant effect between profitability and financial performance variables on firm value. And there is a significant influence between the leverage variables on firm value. There is a significant influence between profitability variables on firm value through financial performance as an intervening variable. And there is no significant effect between leverage variables on firm value through financial performance as an intervening variable